Feminist imaginings in the face of automation and the “end of work”: de-automating reproduction and reorganizing kinship - Silva Massacese, María Julieta (2023)
Automation is once again raising concerns about the threat it poses to employment. Feminists in the 20th century believed that technology could liberate women from undesirable labor. However, historically, industry and automation have not reduced women’s workloads but have instead favored unpaid work, flexibility, and work overload. Rather than mitigating the care and ecological crises, technological development has exacerbated them. This raises an important question for feminist theory: should technology be rejected as a way of reducing women’s workload? To explore this, we analyze classical and contemporary contributions from feminist theorists on the future of work and technology. Using philosophical and feminist theoretical methods, our aim is to examine the relationships between these imaginings and home, family, design, and consumption. This article argues that a feminist analysis of work must include the technological dimension, considering the production of human beings as a strategic technology for feminist purposes. To imagine an alternative near future, the article draws on Donna Haraway’s making kin, emphasizing defamiliarization and refamiliarization of social and ecological relations, pluralist science, and technology for sustainable regeneration of life; and finally, as suggested in this analysis, the ironic persistence of labour in a post-industrial or post-capitalist era.